2021
DOI: 10.1016/j.redox.2021.102206
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione synthesis primes monocytes metabolic and epigenetic pathway for β-glucan-trained immunity

Abstract: Trained monocytes and macrophages produce reactive oxygen species (ROS), which trigger antioxidative glutathione (GSH) response to buffer the rising ROS. However, whether and how the trained immunity is shaped by GSH synthesis remains unknown. Here, we report that β-glucan-trained macrophages from mice harboring a myeloid-specific deletion of the catalytic subunit of glutamate-cysteine ligase ( Gclc) showed impaired GSH synthesis and decreased proinflammatory cytokine production in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Metabolic profiles indicating glycolysis upregulation were also observed in oxLDL‐trained innate immune cells 45,46 . More recently, it was found that impaired glutathione generation compromised mTOR activation, and suppressed β‐glucan‐induced proinflammatory cytokine production and protection against heterologous second challenge 52 . During this process of glycolysis activation, rapamycin might inhibit the mTOR pathway in a dose‐dependent manner to suppress the training effect 50 .…”
Section: Mechanisms Of Trained Immunitymentioning
confidence: 91%
See 2 more Smart Citations
“…Metabolic profiles indicating glycolysis upregulation were also observed in oxLDL‐trained innate immune cells 45,46 . More recently, it was found that impaired glutathione generation compromised mTOR activation, and suppressed β‐glucan‐induced proinflammatory cytokine production and protection against heterologous second challenge 52 . During this process of glycolysis activation, rapamycin might inhibit the mTOR pathway in a dose‐dependent manner to suppress the training effect 50 .…”
Section: Mechanisms Of Trained Immunitymentioning
confidence: 91%
“… 45 , 46 More recently, it was found that impaired glutathione generation compromised mTOR activation, and suppressed β‐glucan‐induced proinflammatory cytokine production and protection against heterologous second challenge. 52 During this process of glycolysis activation, rapamycin might inhibit the mTOR pathway in a dose‐dependent manner to suppress the training effect. 50 In addition, SHIP‐1‐deficient macrophages exhibited increased phosphorylation of Akt, and this correlated with augmented glycolytic metabolism; inhibition of SHIP‐1 could enhance trained immunity.…”
Section: Mechanisms Of Trained Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Oncogenes regulate GLUT1 to intervene the glucose intake and tumor cell metabolism. The c-myc induces GLUT1 overexpression leading to increased glucose uptake ( Leen et al, 2013 ; Huang L et al, 2021 ; Su et al, 2021 ). P53 can inhibit GLUT1 expression in cells, resulting in decreased glucose uptake and thus inhibiting tumor development ( Feng et al, 2018 ).…”
Section: Glucose Metabolism In Neoplastic Cellsmentioning
confidence: 99%
“…C-myc can regulate the transcriptional process of various glycolytic genes ( Gu et al, 2017 ). C-myc can bind to the regulatory region of hexokinase 2 (HK2) and thus play an essential role in tumor aerobic glycolysis ( Huang WL et al, 2021 ; Su et al, 2021 ). PK catalyzes the final step of glycolysis, PKM2, which is only found in self-renewable groups such as stem cells and tumors ( Li et al, 2017 ; van Niekerk and Engelbrecht 2018 ).…”
Section: Tumor Aerobic Glycolytic Signaling Pathwaymentioning
confidence: 99%